Analyzing The Factors Affecting Farmer Engagement in Farm Insurance in Karangsari, Banyumas - Ramadhan, Dicky Satria; Istiqomah; Alfarisy, Muhammad Farid (Jurnal Penyuluhan, 2025)
Agriculture is a sector characterized by uncertainty and high risk. One of the government policies aimed at mitigating this risk is the farm insurance program. Karangsari Village in Kembaran is one of the areas that actively implements this program. However, participation in farm insurance in Karangsari Village is not optimal. This study aims to analyze the influence of age, education, farmers' activeness in groups, farming experience, land area, and land ownership status on participation in farm insurance. These characteristics are considered distinguishing variables that are thought to affect farmer participation. The samples for this study were determined using Taro Yamane. The analysis method employed is logistic regression to assess how age, education, farmers' activeness in groups, farming experience, land area, and land ownership status impact participation in farm insurance. The results showed that age, education, and farming experience did not have a significant effect on farmers' participation in farm insurance, while farmers' activeness in groups, land area, and land ownership status did have a significant effect. In this context, farmers with potential agricultural assets are more likely to participate in farm insurance.